2006
DOI: 10.1099/vir.0.81624-0
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of severe acute respiratory syndrome-associated coronavirus with dendritic cells

Abstract: Severe acute respiratory syndrome (SARS) of humans is caused by a novel coronavirus of zoonotic origin termed SARS-associated coronavirus (SARS-CoV). The virus induces severe injury of lung tissue, as well as lymphopenia and destruction of the architecture of lymphatic tissue by as-yet-unknown mechanisms. In this study, the interaction of SARS-CoV with dendritic cells (DCs), the key regulators of immune responses, was analysed. Monocyte-derived DCs were infected with SARS-CoV and analysed for viability, surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
103
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 44 publications
9
103
1
1
Order By: Relevance
“…It is also consistent with a role of virally encoded proteins in suppressing the type I IFN response, as UV treatment abolishes the ability of the viral RNA to replicate and to act as a template for protein production. We, and others, have previously shown that productive viral infection is not required for DC activation and type I IFN induction, since these can occur even in response to entrycompetent UV-inactivated virus but not in response to entrydeficient virus (29,70). The results obtained with the DLP-, TLP-, and UV-treated RRV preparations in this study are consistent with these results.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It is also consistent with a role of virally encoded proteins in suppressing the type I IFN response, as UV treatment abolishes the ability of the viral RNA to replicate and to act as a template for protein production. We, and others, have previously shown that productive viral infection is not required for DC activation and type I IFN induction, since these can occur even in response to entrycompetent UV-inactivated virus but not in response to entrydeficient virus (29,70). The results obtained with the DLP-, TLP-, and UV-treated RRV preparations in this study are consistent with these results.…”
Section: Discussionsupporting
confidence: 82%
“…However, type I IFN also play a role in driving the generation of adaptive immune responses (45-49, 61, 65), a process during which dendritic cells (DCs) play a central role. Studies have shown that virus exposure stimulates DCs to upregulate the surface expression of costimulatory molecules (11,29,52,70) and that type I IFN are important for mediating this effect (30,31). Viruses that encode type I IFN antagonists may therefore induce suboptimal immune responses not only in the early phase of the infection but also in terms of longterm adaptive responses, as recently discussed for influenza virus and its type I IFN antagonist, nonstructural protein 1 (NS1) (19).…”
mentioning
confidence: 99%
“…This suggests that the abortive infection is terminated prior to the expression of detectable levels of viral gene products. This result confirms and extends the previous work of Law et al and Spiegel et al [13], [14], [22]. The implication is that direct infection of hDCs by SARS-CoV may only marginally contribute to the induction of any cellular immune response, in contrast to HCoV-229E, which has been shown to efficiently stimulate CD8 + T cells following infection of hDCs [24].…”
Section: Discussionsupporting
confidence: 91%
“…Infection of hDCs with SARS-CoV has been shown to be abortive and replication is only barely detectable [13], [14], [22]. However, it is not known to what extent SARS-CoV gene expression can occur in hDCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation